KAJIAN STABILITAS TUMPUKAN BATU DALAM AIR - Pranoto Samto Atmojo (TEKNIK, 2008)
Rock fill Dam, Coffer Dam, Groyne, Railway are example of structures composed by stone material. Rockfill structures are commonly stable enough, but when that’s constructed in under water, than stability ofstructure will decrease significant. Stability of stone structure under water actually depend on by somevariable these are depth of flooding, size or dimension, and stone position. The Author here will show withRail way stabilities calculation for example. Trial by two level position of flooding ,assume diameter stoneand gated value of properties , the result is stone with diameter 12 cm, will scour by less than 20 cm underwater. The Stone will scours by the flowing water if the velocity of water (Va) bigger than Critical velocityof the stone (Ucr). At the reality, rail way structured by stone with variation size more or less from 5 to 12cm, and depth of flooding possible occur more than 20 cm. So, rail way potential hanging cause of stonesupporting scour by flooding however only 10 cm depth. Calculation of stone stabilities used after Isbash,Goncharov,Levi dan Maynord formulae.